Child protection in America: past, present, and future - Myers, John E. B. (Oxford University Press, 2006)
Child protection from the colonial period to 1875 -- Societies for the prevention of cruelty to children -- Child protection from 1900 to 1962 -- Child protection from 1962 to the present -- Child sexual abuse -- Causes of child abuse and neglect -- Reducing abuse and neglect -- Improving the child protection system.